The Manuscript "al-Kanz al-Jalil ’ala Madarik al-Tanzil Wa Haqa’iq al-Ta’wil Li Abi Al- Barakat al-Nasafi" Authored by Ibrahim ibn Ibrahim al-Janaji: Study and Investigation - Billah, Md. Masum; Ali al-Gamidi, Muhammad (Eximia, 2021)
This study investigates the interpretation of Surat al-Mujadalah from the verse number (8) to (13) from the manuscript "al-Kanz al-Jalil 'ala Madarik al-Tanzil wa Haqa'iq al-Ta'wil li Abi al-Barakat al-Nasafi" authored by Ibrahim ibn Ibrahim al-Janaji known by Busailah, who is one of the great scholars of al-Azhar al-Sharif. He is an interpreter, jurist, philosopher, and linguist. The author exposed the cover from the unclear concepts of al-Nasafi in his interpretation and added definitions of the surahs, the relations between the surahs or verses, the meanings of the verses from the reliable books of interpretation, the verses related to juristic and creedal issues related to the verses, and the types of common and unusual readings of the verses. The methods used in this study are: keeping the Tafsir al-Nasafi in bold, then followed by the explanation of Imam Ibrahim Busaylah, and the process of investigation in the footnotes; trusting on the lone copy of manuscript and strengthening its loneliness by matching it with its sources and the author's sources from which it was quoted, including the proof of differences and completing the shortage in his explanation; copying the manuscript according to the modern orthographic writing system with controlling the formation; attributing the Qur'anic verses to their Surahs including their numbers with writing them following the font of "Mushaf al-Madinah al-Nabawiyyah"; authenticating the sayings and various opinion of the scholars from their original sources if possible, otherwise from the secondary sources; and remarking on the issues contained in the manuscript while it is needed. The most important findings of this study are: Imam Abu al-Barakat al-Nasafi is considered one of the great exegetes who were concerned with the study of the science of interpretation and were acquainted with it, that why they brought it out in the most beautiful way; 'Madarik al-Tanzil wa Haqa'iq al-Ta'wil' is counted as a valuable and most important interpretation book of the Qur'an, as he was famous for his maintenance of advancement, explanation, teaching and summarization; 'al-Kanz al-Jalil 'ala al-Madarik al-Tanzil' is calculated as a most significant explanation book of 'Tafsir al-Nasafi'; the author of "al-Kanz al-Jalil" has followed uncommon methods to write this book; and The verses selected for investigation remind the people etiquette of conversing, assemblies, and conversing with the Messenger (PBUH) with mention the knowledge of Allah (SWT) regarding everything.